Ibu Sehat Janin Sejahtera melalui Optimalisasi Pemeriksaan Antenatal Care - Gayuh Sasiwi, Adhe Lisna; Wulansari, Meinita; Isini, Firdayanti; Mootapu, Mu’min; Jeane Rott, Junike i; Tuwongkesong, Dewi Asti; Datau, Lidianty; Kansil, Tirza; Dewi Mangkey, Tirza Wulan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Antenatal Care (ANC) services are health services that can prevent problems during pregnancy. They aim to fulfill the right of every pregnant woman to receive quality antenatal care, ensuring a healthy pregnancy, safe delivery, and the birth of a healthy baby. These services include maternal and child health care, nutrition, infectious disease control, and non-communicable disease management, as well as several other local and specific programs. Method: To increase the visits of pregnant women for routine examinations of the mother and fetus. Pregnancy examinations/ANC, Hb level examinations, counseling, and the provision of supplementary food. This activity was conducted in collaboration with the Bolaang Mongondow Timur Health Office. The participants were 6 pregnant women. Results: After conducting standard antenatal care and Hb examinations on 6 pregnant women, it was found that 5 of them were anemic. Therefore, health education was provided to address anemia, along with iron tablets and red spinach noodles as supplementary food. Additionally, pregnant women were given counseling to prevent stunting during the first 1000 days of life. Conclusion: The activities were carried out smoothly and received positive feedback from the pregnant women. It is hoped that through this community service activity, the health status of pregnant women can be improved.